Timing of onset of cognitive decline: results from Whitehall II prospective cohort study. (5th January 2012) - Singh-Manoux, Archana; Kivimaki, Mika; Glymour, M Maria; Elbaz, Alexis; Berr, Claudine; Ebmeier, Klaus P; Ferrie, Jane E; Dugravot, Aline
Abstract : Objectives To estimate 10 year decline in cognitive function from longitudinal data in a middle aged cohort and to examine whether age cohorts can be compared with cross sectional data to infer the effect of age on cognitive decline. Design Prospective cohort study. At study inception in 1985-8, there were 10 308 participants, representing a recruitment rate of 73%. Setting Civil service departments in London, United Kingdom. Participants 5198 men and 2192 women, aged 45-70 at the beginning of cognitive testing in 1997-9. Main outcome measure Tests of memory, reasoning, vocabulary, and phonemic and semantic fluency, assessed three times over 10 years. Results All cognitive scores, except vocabulary, declined in all five age categories (age 45-49, 50-54, 55-59, 60-64, and 65-70 at baseline), with evidence of faster decline in older people. In men, the 10 year decline, shown as change/range of test×100, in reasoning was −3.6% (95% confidence interval −4.1% to −3.0%) in those aged 45-49 at baseline and −9.6% (−10.6% to −8.6%) in those aged 65-70. In women, the corresponding decline was −3.6% (−4.6% to −2.7%) and −7.4% (−9.1% to −5.7%). Comparisons of longitudinal and cross sectional effects of age suggest that the latter overestimate decline in women because of cohort differences in education. For example, in women aged 45-49 the longitudinal analysis showed reasoning to have declined by −3.6% (−4.5% to −2.8%) but the cross sectional effects suggested a decline of −11.4% (−14.0% to −8.9%). Conclusions Cognitive decline is already evident in middle age (age 45-49).